Genetic Manipulation of Ticks: A Paradigm Shift in Tick and Tick-Borne Diseases Research - Nuss, Andrew; Sharma, Arvind; Gulia-Nuss, Monika (Frontiers in Cellular and Infection Microbiology, 2021)
Ticks are obligate blood-feeding arthropods that are distributed worldwide and one of the most important vectors of pathogens affecting humans and animals. Globally, emerging and re-emerging tick-borne diseases exert an enormous impact on public health. Tick populations are expanding their range due to changes in climate and new tick-borne diseases are emerging. However, despite the growing burden of tick-borne diseases, research on ticks has lagged behind other arthropod vectors, such as mosquitoes, largely because of a lack of genetic and molecular tools. CRISPR-Cas9 is transforming non-model organism research; however, successful germline editing has not yet been reported in ticks. Here, we are reviewing the ancillary methods needed for transgenic tick development and the use of CRISPR/Cas9, the most promising gene-editing approach, for tick genetic transformation.